Analisis Resepsi Khalayak Terhadap Nilai Kecantikan Pemeran Utama “Ariel” dalam Film “Little Mermaid 2023” - Nuril Madania; Heidy Arviani (J-CEKI : Jurnal Cendekia Ilmiah, 2025)
The Little Mermaid 2023 is a film that tells the story of the love journey of the mermaid Ariel and Prince Eric which is hindered by differences in the nature of life. This film illustrates that love is not hindered by boundaries and must be fought for. The main object (main character) in this film is a woman who has a different physical character from the animated series, thus causing a debate in the public. So this research aims to find out the public's opinion about the main character Ariel in a different version of the film with the animated characters that have been inherent in the imagination of each individual. The type of research carried out is qualitative descriptive research. Type of research is qualitative descriptive research method is a research method used to examine an object with the aim of describing, explaining and answering in detail the problem being studied. Keywords: Reception, Audience, Representatio